Farmed and Dangerous? A Case Study of Chipotle’s Branded Entertainment Series and Polarized Reactions to its Satirical Depiction of Farming and Agribusiness - Nathan Gikerson; Rebecca Swenson; Betsy Anderson (Journal of Applied Communications, 2016)
This study follows Chipotle’s innovative strategy of using branded entertainment and satire to enhance its brand image and positive consumer perceptions, while negatively portraying an entire industry. The study explores audience reactions to Chipotle’s satirical Farmed and Dangerous program, part of the company’s broader “Food with Integrity” campaign. Increasing agricultural literacy and understanding among the general public is a priority (Doerfert, 2011). Yet marketing communication campaigns—and responses or reactions to those campaigns—that simplify issues into distinct “sides,” or focus on attacks, prevent deep discussion of the complexity of our food system and efforts to collaborate on solutions. Research presented uses a case study, supported by focus group methodology and in-depth survey responses of YouTube commenters, to examine consumer and stakeholder reactions to Chipotle’s content. Findings reveal sharply divided reactions and significant anger and frustration within the agricultural community toward Chipotle for its satirical portrayal of the food production industry. Findings also reveal generally positive attitudes toward Chipotle from those without agricultural experience, and clear perceptions of “sides” in the food debate. Discussion of Chipotle’s marketing strategy explores whether the negative sentiment the company has generated among agricultural stakeholders through efforts like its Farmed and Dangerous webisode series is worth it for the brand, considering the broader positive image the company has gained among much of the general public, as well as related implications for the company linked to more recent struggles with food safety issues and attacks from political groups.
Keywords: Agriculture Communication; Branded Entertainment; Food Marketing; Public Relations; Satire; Sustainability